Konsep Manajemen Pendidikan Islam dalam Al-Quran dan Hadis - Ma'ruf, M. (Didaktika Religia, 2015)
This paper discusses the concept of management from the lens of Qur’an andHadith that have become reference and way of Muslim life. Islamic education witha variety of pathways, levels, and forms all need good management; otherwise,negative image of Islamic education will always remains. Though, the Qur’an andthe Hadith did not mention management in detail, the basics of management havebeen stated in the Qur’an and the Hadith such as planning, leadership patternsrelated to the life of the organization, implementation and evaluation.Key words: Management, Islamic education, al-Qur’an, Hadith